Studi Populasi Monyet Ekor Panjang (Macaca Fascicularis) Di Pulau Condong Darat Desa Rangai Kecamatan Ketibung Kabupaten Lampung Selatan - Risdiyansyah Risdiyansyah; Sugeng Prayitno Harianto; Nuning Nurcahyani (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
The Condong Terestrial Island is one of the island belong to tourist area, Pasir Putih, in Rangai village. This island has a natural vegetation and become conservation area for all living things.One of them is the long tailed macaques (Macaca fascicularis), or the crab-eathing macaques. The objective of this research is to know about the number and the population density of long tailed macaques (Macaca fascicularis) at Condong Terestrial Island. The research has been done from January 16th to February 5th 2012. This research was using concentrated method. Data was collected by visiting the existence of long tailed macaques. Population of longtailed macaques was calkulated by noting the time and the number of individuals admitted at any point of observation, the number of crab-eating macaques in and out at any poin wast recorded on tally sheets to avoid repetition of the calculation. The observation was conducted during the daytime started from 6am to 6pm. The result of this research shown that the total number of this long tailed macaques is about 140 individu with population density is about 28 ekor per hectare. Keywords: Condong Island, Macaca fascicularis, population density, population study